Circulating microparticles in carriers of prothrombin G20210A mutation - Campello, Elena; Spiezia, Luca; Radu, Claudia M.; Gavasso, Sabrina; Zerbinati, Patrizia; Woodhams, Barry; Simioni, Paolo (Thrombosis and Haemostasis, 2014)
Factor V Leiden (FVL) and prothrombin gene mutation G20210A (PTM) are the two most common genetic polymorphisms known to predispose carriers to venous thromboembolism (VTE). A recent study in FVL carriers showed that circulating levels of microparticles (MP) may contribute to their thrombogenic profile. To further elucidate the prothrombotic state linked to genetic thrombophilia, we extended this study to carriers of PTM. The plasma level of annexin V-MP, endothelial- MP (EMP), platelet-MP (PMP), tissue factor-bearing MP (TF+) and the MP procoagulant activity (PPL) was measured in 124 carriers of PTM (105 heterozygous and 19 homozygous) and in 120 age- and gender-matched healthy individuals. Heterozygous and homozygous carriers of PTM showed significantly increased levels of annexin V-MP (2930 [1440–4646] MP/μl and 3064 [2412–4906] MP/μl, respectively) and significantly shorter PPL clotting time (54 [46–67] sec and 55 [46–64] sec) compared to controls (1728 [782–2122] MP/μl and 71 [61–75] sec, respectively; p<0.01). Similarly, heterozygous and homozygous subjects presented with significantly higher levels of EMP, PMP and TF+ than controls (p<0.05). PTM carriers with a VTE history had significantly higher MP numbers and activity than controls. No significant difference was seen between carriers with and without a VTE history. We conclude that the higher levels of circulating MP found in PTM carriers may play a role in the development of VTE possibly by increasing thrombin generation. Further studies are needed to better define the role of MP as triggering factors for the thrombotic complications characterizing mild genetic thrombophilic defects.
Keywords: Hypercoagulability; microparticles; thrombophilia; venous thrombosis